EFFECTIVENESS OF THE DUOLINGO APP IN LEARNING THE ARABIC LANGUAGE: APPROACHES AND ANALYSIS (The Journal of Interdisciplinary Human Studies, 2026)
This article provides an in-depth analysis of the methods for assessing theeffectiveness of using the Duolingo mobile application in the process of teaching Arabic.In particular, in the development of digital technologies, the features of educationalapplications based on gamification and interactive, interesting approaches to thedevelopment of students’ language skills are highlighted. In addition, the learningoutcomes, motivation, and activity of students using the Duolingo application andtraditional teaching methods are compared using tests and data obtained from practicalexperience. This article contributes to enriching innovative strategies in Arabic languagepedagogy and offers teachers scientifically based recommendations for more effectiveintegration of technologies.
Keywords: Duolingo; gamification; Arabic; educator; student; learning; approach